Efeito estressor do glifosato e paraquate em Saccharomyces cerevisiae - Ianoski, Aline Bisinella (2019)
Glyphosate and paraquat are herbicides used in many countries. The disposal of these products and their metabolites lead to the contamination of several environmental compartments, and are often conducted to sewage and water treatment plants. Studies report that exposure to these compounds may lead to oxidative stress in organisms. An exaggerated stimulus in the production of free radicals, such as reactive oxygen species (ROS), may be related to more than fifty diseases. One way to monitor the effect of these micropollutants on living things is to employ Saccharomyces cerevisiae as a eukaryotic model. In this context, this yeast was used to evaluate the stressor effect generated by the micropollutants glyphosate and paraquat, both with the analytical standards and with its commercial formulations TROP® and TOCHA®, respectively. Cell survival analyzes were performed at different time periods, from the generation of ROS and the determination of the catalase (CAT) and superoxide dismutase (SOD) enzymes after 2 and 3 hours of exposure to the pesticides. For the cell survival assay the cells from the logarithmic growth phase were treated with the analytical standards glyphosate and paraquat at the concentrations of 50, 100 and 200 μmol L-¹. The concentration that most affected the growth rate of the yeast was 200 μmol L-¹, and this was the concentration applied in the other assays. In the survival trials with the commercial formulations TROP® (glyphosate) and TOCHA® (paraquat) the cell growth rate was drastically affected. There was an increase in the production of ROS during the second and third hour of exposure to almost all the compounds analyzed, except for the paraquat analytical standard in the second hour. CAT production in the second hour increased only to the glyphosate analytical standard, and in the third hour it increased for both the substance and the TROP® commercial formulation. For the other substances studied, there were no significant changes in CAT production. The enzyme SOD increased in the presence of the analytical standards glyphosate and paraquat in the second hour, and in the third hour there was a significant reduction in the enzymatic activity against analytical paraquate. Commercial formulations TROP® and TOCHA® showed no significant difference in the prodution of SOD in relation to the control in any of the analyzed periods. The results obtained show that there is a need to address not only the active ingredients of pesticides, but especially their commercial formulations, as this is how pesticides are made available in the environment.